2019
DOI: 10.1111/idj.12487
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in dental care – the role of vicarious trauma

Abstract: Objectives In health care, empathy is associated with compassion, thoughtfulness, attentiveness and caring. While empathy is perceived as desirable and positive, it can potentially be associated with negative aspects, such as secondary traumatic stress or vicarious trauma (VT). VT addresses the secondary vicarious influences of patients’ pain and discomfort on clinicians. Dentists are routinely exposed to patients’ anxiety, pain and discomfort. These may lead to VT, which in turn can affect empathy. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that age was related to high empathy levels as older dentists become more experienced, and more self-confident with higher self-efficacy. 5,23,27 Research conducted on adults from 63 countries was performed by three American universities and ranked Saudi Arabia second in empathy level. 47 However mean score of empathy levels of Saudi students was lower than the dental students in other countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that age was related to high empathy levels as older dentists become more experienced, and more self-confident with higher self-efficacy. 5,23,27 Research conducted on adults from 63 countries was performed by three American universities and ranked Saudi Arabia second in empathy level. 47 However mean score of empathy levels of Saudi students was lower than the dental students in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the purpose of this research is to study the empathy levels of dental interns and postgraduate students given their critical transitional period and different career demands. While previous studies have shown that age and females as gender were related to high empathy levels, 5,23,27 we hypothesized that females and older participants, whether they are interns or postgraduate students, will be more empathetic. Also based on several researches 8,12,17 we hypothesized that graduate students may have a lower level of empathy because of their workload which may impair or lower their empathetic tendencies.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The premise of solid empathy training for professors could be a factor contributing to increase the possibility of success in clinical activity by their students. In this case, the professor executes actions that end up presenting positive attitude models for their students and strengthening their educational process [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The foregoing ideas imply that empathy training for students must constitute an ongoing objective for universities and become manifest as an effective policy related to the incorporation of empathy into training of all Health Sciences careers [1,2,[4][5][6][7][8][9][10][11]. In keeping with the above, the American Dental Education Association (ADEA) [12] has stated that empathy is the second essential clinical competency for all dentists.…”
Section: Introductionmentioning
confidence: 99%